2022
DOI: 10.1093/cid/ciac110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of BNT162b2 and mRNA-1273 Second Doses and Boosters for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection and SARS-CoV-2–Related Hospitalizations: A Statewide Report From the Minnesota Electronic Health Record Consortium

Abstract: Using vaccine data combined with electronic health records, we report that mRNA boosters provide greater protection than a two-dose regimen against SARS-CoV-2 infection and related hospitalizations. The benefit of a booster was more evident in the elderly and those with comorbidities. These results support the case for COVID-19 boosters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…After excluding 1857 duplicates and screening of title and abstract of the remaining 2191 studies, we retained 97 full texts that met our inclusion criteria for review of eligibility. After exclusion of irrelevant studies, due to various reasons such as missing outcome of interest or missing information on people with diabetes, 12 studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were included in the review. Through citation searching of included articles, five additional studies [ 31 , 32 , 33 , 34 , 35 ] were identified and included, resulting in a total of 17 studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding 1857 duplicates and screening of title and abstract of the remaining 2191 studies, we retained 97 full texts that met our inclusion criteria for review of eligibility. After exclusion of irrelevant studies, due to various reasons such as missing outcome of interest or missing information on people with diabetes, 12 studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were included in the review. Through citation searching of included articles, five additional studies [ 31 , 32 , 33 , 34 , 35 ] were identified and included, resulting in a total of 17 studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…VE for hospitalization ranged from 35 to 96% in persons with diabetes and from 67 to 93% in the total population or persons without diabetes. In three of four studies, VE estimates were lower in persons with diabetes compared to the total population, with large and significant differences in one study [ 22 ]. VE for death ranged from 53 to 93% in persons with diabetes and from 39 to 97% in the total population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our estimate is similar to the reduction in cumulative incidence of reported infections associated with booster vaccination during an Omicron wave in Los Angeles County [ 33 ] and consistent with a pooled estimate of booster effectiveness (47%; 95% CI: [19%, 65%]) from a meta-analysis of studies completed during periods of Omicron predominance across the globe [ 34 ]. Importantly, our analysis includes both symptomatic and asymptomatic infections because the student population was under active surveillance, whereas none of the studies included in the meta-analysis examined a population under active surveillance [ 7 , 35 40 ]. Interestingly, between two studies on the effectiveness of a second booster dose, i.e., fourth vaccine dose [ 41 , 42 ], one that used data collected during active surveillance [ 42 ] also found lower effectiveness than one that did not [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor —We read with great interest the recent article by Drawz et al in which the authors explored the potential role of messenger RNA (mRNA) vaccine’s booster doses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)–related hospitalizations [ 1 ]. In South Korea, a coronavirus disease 2019 (COVID-19) vaccination campaign was initiated starting on 26 February 2021.…”
mentioning
confidence: 99%